Income approach and property market cycle - D’amato, Maurizio (International Journal of Strategic Property Management, 2015)
This paper is focused on a proposed valuation method including real estate market cycle analysis in real estate valuation process. Starting from early works on this field (d'Amato 2003) the work highlight the dangerous gap between academic research on property market cycles and professional practice of property valuation. The danger of this gap comes from the fact that in spite it is well documented that the property market has a “natural” cyclical behaviour, the opinions of value based on income approaches still relies on assumption of a stable or perpetually growing (or decreasing) income. This may be one generating factors of the real estate bubble and the subsequent financial markets crisis experienced recently. This paper offers a general introduction on cyclical capitalization as a further family of valuation methodologies based on income approach. This method includes in the traditional Dividend Discount Model more than one g-factor in order to plot property market cycle. An empirical application of Cyclical Capitalization is offered to the office market of the Eastern London.First Publish Online: 9 Oct 2015